BUMBUDENDRON MILLANI (ARRONDO ET PETRIELLA) N. COMB., DEL CARBONICO-PERMICO DE ARGENTINA Y BRASIL. (Ameghiniana, 2014)
Lycopodiopsis millani Arrondo et Petriella, is generically reallocated to Bumbudendron Archangelsky, Azcuy et Wagner. The presence of an infrafoliar bladder provides de main supporting character for the new combination. The nearest species to Bumbudendron millani is perhaps B. nitidum; this species differs in several features: phyllotaxis, dimensions and length/breadth ratio and the shape of the infrafoliar bladder